Analysis of Moral Value in Song Lyrics Seperti Pelangi Habis Hujan by Natahsia Nikita - Abdul Rahman Hatsama; Tresia Anita Baru (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
This study aims to analyse the moral values in song lyrics such as the rainbow after the rain by Natahsia Nikita. This type of research is qualitative research so it will produce descriptive data in the form of words. The data analysed in it is descriptive and not in the form of numbers. The research is a study by lecturers and students in the seventh semester of the 2020/2021 academic year, Universitas Pendidikan Muhammadiyah Sorong. Data collection techniques using library techniques, listening, and noting, and documentation. Data analysis using the interactive model technique Miles and Huberman state that qualitative data analysis uses words that are always arranged in an expanded or described text. When giving meaning to the collected data, the data is analysed and interpreted. Data analysis includes the following stages: (1) data reduction, (2) display/presentation of data, and (3) drawing conclusions and then verifying. The message in song lyrics contained in the lyrics of the song by Natahsia Nikita brings a good moral message to us, namely, we must live this life patiently, we must also respect each other both parents and others, and we are also taught to be able to forgive and forgive others. And fully live this life by God'swill as for the other moral values above, such as the values of trust, fairness, compassion, honesty, trust, patience, brotherhood, unity, and tolerance between religious communities and so on, and can be implemented in the present and future life. which will come.